How does income distribution affect economic growth? Evidence from Japanese prefectural data - Masako Oyama (Osaka University, Institute of Social and Economic Research (ISER), 2014)
There have been various empirical researches on the effects of income distribution on economic growth. Although studies using cross-country data used to be common, recent researches started to use regional panel-data within one country. This paper uses Japanese prefectural panel data to analyze how income distribution affects economic growth. The measures of the income distribution used in the estimations are the income share of the third quintile and the Gini indices. In the fixed effects estimations and the GMM estimations, the income share of the third quintile has positive and statistically significant effects on five-year economic growth rates. On the other hand, the Gini indices have positive and statistically significant effects on both of the five-year and ten-year economic growth rates in the fixed effects estimations, and negative effect on the five-year growth rate in the GMM once. These results are the similar to one of the existing literatures and can be explained with the modified median voter theory.
Keywords: O40; C33; J01; 330